Peningkatkn Aktivitas dan Hasil Belajar IPA melalui Student Facilitator and Explaining pada Siswa Kelas V SD Negeri 39 Gedong Tataan, Pesawaran - Sugi Lestari (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2022)
This research was conducted with the aim of increasing science learning activities and outcomes at SDN 39 Gedong Tataan, Gedong Tataan District, Pesawaran Regency, as well as to increase teacher creativity and performance in learning activities. From the results of observations of student activity increased 6.7% in the first cycle, 10.75% in the second cycle, and 26.25% in the third cycle. Likewise, student learning outcomes showed an increase from an average of 64.70 to 68.23 with only 50% of students who completed the first cycle. In the second cycle the learning outcomes became 69.41 and 73.52 in the third cycle with students who completed 83.33%. 39 Gedong Arrangement for the 2019/2020 school year.